OPTIMIZATION OF THE SURGICAL TECHNIQUE OF EXTRAVESICAL URETERAL REIMPLANTATION - KH.M. MIRAKOV (Avicenna Tajik State Medical University, 2022)
Objective: To optimize the technique of extravesical ureteral reimplantation in experimental animals. Methods: Experiments were carried out on 21 Flanders rabbits. Initially, ureterohydronephrosis (UHN) was modeled by alcoholization of the ureter in its vesical part according to the method of Ya.V. Gudynsky. After 21 days, the animals underwent extravesical ureteral reimplantation using the technique optimized by the team of urologists. Results: The stents were removed endoscopically on the 20th day. In order to exclude vesicoureteral reflux, contrast cystography was performed, in which reflux was not detected. To exclude obstruction, on the 30th, 60th, and 90th days after the operation, an ultrasound scanning of the urinary system was performed, in which the presence of UHN was not noted. On the 90th day, the experimental animals underwent resection of the anastomotic zone for histological examination. It was found that the diameter of the transplanted segment corresponded to the normal size of the rabbit ureter, there was a slight thickening of the ureteric wall, its hypertrophy, and intracellular hyperplasia. Conclusion: The effectiveness and safety of the proposed method of extravesical ureteral reimplantation with antireflux protection has been experimentally proven.